Addendum to “Leaf insects from Luzon, Philippines, with descriptions of four new species, the new genus Pseudomicrophyllium, and redescription of Phyllium (Phyllium) geryon Gray, 1843, (Phasmida: Phylliidae)” - Cumming, Royce T.; Leong, Jing V.; Lohman, David J. (Zootaxa, 2018)
At the time Cumming et al. (2017) was published, the GenBank accession numbers for partial cytochrome c oxidase subunit I (COI) DNA barcode sequences from Microphyllium specimens sampled in the phylogenetic analysis were not yet available. This information is provided in Table 1.